A real-time PCR assay based on a specific mutation of PstS1 gene for detection of M. bovis strains. (March 2020) - Ji, Lingyun; Jiang, Yi; Li, Guilian; Zhao, Xiuqin; Wan, Kanglin
Abstract: The Mycobacterium tuberculosis complex (MTBC) is composed of several genetically related and pathogenic mycobacterial species, including M. tuberculosis, M. bovis and M.africanum et al. In our previous study, we found that M. bovis strains had a unique SNP located in position 1055 in the sequence of the pstS1 gene in which a T was substituted by a C. In this study, specific primers and MGB probes were designed according to the mutation in PstS1 gene, and a sensitive, specific and rapid real-time PCR assay for M. bovis was established. Then the assay was used to detect M. bovis in simulation samples. The minimum detectable concentration is 10 1 copies for M. bovis DNA. The standard curve showed correlation coefficient between threshold cycle and PstS1 gene fragment copy number was 0.997 and slope is −3.144. The minimum detectable concentration is 10 1  cells/ml for simulation sample. In addition, M.bovis strain 93006, 14 clinical BCG stains and 7 clinical M.bovis strain showed positive while the other strains showed negative results, which proved good specificity. This assay had high sensitivity and specificity for identification of M. bovis from the simulation specimens. The assay can be applied for epidemiological and ecological surveillance of M. bovis strains.